High temperature transformations of the Au7Cu5Al4 shape-memory alloy - Cortie, M.; Kealley, Cat; Bhatia, V.; Thorogood, G.; Elcombe, M.; Avdeev, M. (Elsevier B.V., 2011)
The beta-phase of Au7Cu5Al4 undergoes a reversible shape-memory phase transformation, however there has been some uncertainty regarding the crystal structure or structures of the parent phase. Here we show that, under equilibrium conditions, the parent phase possesses the L21 structure between its Ap (about 79 degrees C) and ~630 degrees C, and the B2 primitive cubic structure between ~630 degrees C and its melting point. It melts directly from B2 into the liquid state and hence never achieves the random bcc A2 structure that has been previously mooted. Splat-cast samples of the alloy are martensitic, proving that development of equilibrium order and defect concentration are not pre-requisites for the A->M transformation to occur